2020
DOI: 10.1111/jphp.13347
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency comparison of apigenin-7-O-glucoside and trolox in antioxidative stress and anti-inflammatory properties

Abstract: Objectives Chamomile has long been used as a medicinal plant due to its antioxidative and anti-inflammatory activity. Apigenin-7-O-glucoside (AG) is one of the major ethanol extract components from chamomile; however, the underlying mechanism remains unclear. Methods In this study, the antioxidant potential and the anti-inflammatory activities of AG were analysed and compared with those of trolox. We demonstrate the protective effects of AG on free radical-induced oxidative damage of DNA, proteins and erythroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…It is found in various natural sources like vegetables and fruits ( Funakoshi-Tago et al, 2011 ). There are number of pharmacological activities like antidiabetic ( Choi, et al, 2014 ), anticancer ( Lu et al, 2020 ), anti-oxidant ( Darabi et al, 2020 ) and anti-inflammatory activity ( Wang et al, 2020 ) have been reported. It has poor aqueous solubility and belongs to BCS-II class category ( Huang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is found in various natural sources like vegetables and fruits ( Funakoshi-Tago et al, 2011 ). There are number of pharmacological activities like antidiabetic ( Choi, et al, 2014 ), anticancer ( Lu et al, 2020 ), anti-oxidant ( Darabi et al, 2020 ) and anti-inflammatory activity ( Wang et al, 2020 ) have been reported. It has poor aqueous solubility and belongs to BCS-II class category ( Huang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory effects of chamomile preparations or their isolated compounds have been identified in studies of multiple experimental models (Miguel et al, 2015[ 90 ]; Wang et al, 2020[ 138 ]; Cavalcante et al, 2020[ 17 ]) and when used to treat various diseases associated with the development and progression of inflammatory processes (Jabri et al, 2020[ 54 ]; Wang et al, 2020[ 138 ]). For example, treatment of macrophages with lipopolysaccharide (LPS) from Escherichia coli is a well-established experimental system for studies of inflammation and stimulates a range of signaling pathways, including NF-κB-mediated signaling that enhances the transcription of mRNA encoding pro-inflammatory cytokines such as IL-1β, IL-6, TNF-α (Tanaka et al, 2014[ 130 ]).…”
Section: Pharmacological Effects Of Chamomile Preparationsmentioning
confidence: 99%
“…The incubation of macrophages with LPS in the presence of polyphenol-rich chamomile extracts or apigenin-7-O-glucoside decreased production of pro-inflammatory cytokines IL-1β, IL-6 and TNF-α (Drummond et al, 2013[ 27 ]; Miguel et al, 2015[ 90 ]). Apigenin-7-O-glucoside also had strong inhibitory effects on LPS-induced NF-κB/NLRP3/caspase-1 signaling in macrophage RAW246.7 cells (Wang et al, 2020[ 138 ]). Moreover, apigenin-7-O-glucoside was found to suppress LPS-induced mRNA expression of iNOS and cyclooxygenase-2 (COX-2), lowering release of inflammatory mediators, • NO and prostaglandin E2 (PGE2) (Hu et al, 2016[ 53 ]).…”
Section: Pharmacological Effects Of Chamomile Preparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a strong inhibitory effect on tumor-cell viability in vivo and in vitro. Its derivative apigenin 7-glucoside has anti-inflammatory, antioxidant and anticancer activities [32]. Apigenin 7-glucoside significantly suppressed the proliferation of HeLa cells, and the IC 50 value at 48 h was 47.26 µmol/L.…”
Section: Flavonesmentioning
confidence: 99%